2007
DOI: 10.1002/anie.200603224
|View full text |Cite
|
Sign up to set email alerts
|

The σ‐CAM Mechanism: σ Complexes as the Basis of σ‐Bond Metathesis at Late‐Transition‐Metal Centers

Abstract: Complexes in which a sigma-H--E bond (E=H, B, Si, C) acts as a two-electron donor to the metal center are called sigma complexes. Clues that it is possible to interconvert sigma ligands without a change in oxidation state derive from C--H activation reactions effecting isotope exchange and from dynamic rearrangements of sigma complexes (see Frontispiece). Through these pathways, metathesis of M--E bonds can occur at late transition metals. We call this process sigma-complex-assisted metathesis, or sigma-CAM, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
532
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(556 citation statements)
references
References 145 publications
(179 reference statements)
23
532
0
1
Order By: Relevance
“…The hydrogenolysis mechanism of a pincer Ir(III)-CH3 complex was analyzed in detail by Brookhart and co-workers (Scheme 36a). Spectroscopic studies and DFT calculations revealed that reductive elimination of methane proceeds through a σ-metathesis or σ-CAM mechanism, 207 in which the oxidation state of iridium is unaltered over the course of the transformation and where a σ-methane complex 3.18b is an instrumental intermediate. 92b The metal-ligand cooperative hydrogenolysis of a Ni-CH3 bond in 3.19 has recently been disclosed and the role of the boryl ligand in assisting such transformation is supported by computational studies (Scheme 36b).…”
Section: Protonolysis and Hydrogenolysismentioning
confidence: 99%
“…The hydrogenolysis mechanism of a pincer Ir(III)-CH3 complex was analyzed in detail by Brookhart and co-workers (Scheme 36a). Spectroscopic studies and DFT calculations revealed that reductive elimination of methane proceeds through a σ-metathesis or σ-CAM mechanism, 207 in which the oxidation state of iridium is unaltered over the course of the transformation and where a σ-methane complex 3.18b is an instrumental intermediate. 92b The metal-ligand cooperative hydrogenolysis of a Ni-CH3 bond in 3.19 has recently been disclosed and the role of the boryl ligand in assisting such transformation is supported by computational studies (Scheme 36b).…”
Section: Protonolysis and Hydrogenolysismentioning
confidence: 99%
“…E is most commonly H, SiR 3 or BR 2 , but in principal this idea extends to C-H s-complexes. 37 Hall has used the atoms-in-molecules (AIM) approach 38 to characterise different transition states in terms of the varying patterns of bond critical points (BCP) and ring critical points (RCP) (see Fig. 6 Despite this elegant outcome, it seems likely that a continuum of transition state structures will be formed as more computational data become available on SBM processes.…”
Section: Overviewmentioning
confidence: 99%
“…2 Thus, coordination of the hydrogen of a silane SiH bond to the coordinatively unsaturated metal center in a complex ML n can lead to the formation of A bearing an η 1 (H)-silane ligand, and then the coordination mode of the silane ligand in A can change to an η 2 -mode to give complex B that has stronger M£Si interaction compared with that in A. Finally, B can be converted either into a hydrido(silyl) complex C via complete oxidative addition or into other types of intermediate via ·-CAM mechanism, 3 etc. Therefore, to understand the detailed reaction mechanism of the SiH activation, it is indispensable to experimentally elucidate how bonding interaction between a metal and an SiH bond (M£H£Si interaction) can gradually change at some different stages of the process.…”
mentioning
confidence: 99%